What Family Circumstances, During COVID-19, Impact on Parental Mental Health in an Inner City Community in London? - Whitaker, Lydia; Cameron, Claire; Hauari, Hanan; Hollingworth, Katie; O'Brien, Margaret (Frontiers in Psychiatry, 2021)
The introduction of lockdown due to a public health emergency in March 2020 marked the beginning of substantial changes to daily life for all families with young children. Here we report the experience of families from London Borough of Tower Hamlets with high rates of poverty and ethnic and linguistic diversity. This inner city community, like communities worldwide, has experienced a reduction or closure in access to education, support services and in some cases, a change in or loss of income, job and food security. Using quantitative survey items (N=992), we examined what differences in family circumstances, for mothers and fathers of young children aged 0-5 living in Tower Hamlets, during March 2020 to November 2020, were associated with their mental health status. We measure parental mental health using symptoms of depression (self-report: Patient Health Questionnaire depression scale: PHQ-8), symptoms of anxiety levels (self-report: General Anxiety Disorder: GAD-7) and perceptions of direct loneliness. We find parental mental health difficulties are associated with low material assets (financial security, food security and children having access to outside space), familial assets (parents time for themselves and parent status: singlelone vs. cohabiting) and community assets (receiving support from friends and family outside the household). South Asian parents and fathers across ethnicities were significantly more likely to experience mental health difficulties, once all other predictors were accounted for. These contributing factors should be considered for future pandemics, where restrictions on peoples lives are put in place, and speak to the importance of reducing financial insecurity and food insecurity as a means of improving mental health of parents.